Application Exercises Improve Transfer of Statistical Knowledge in Real-World Situations. (July 2013) - Daniel, Frances; Braasch, Jason L. G.
The present research investigated whether real-world application exercises promoted students' abilities to spontaneously transfer statistical knowledge and to recognize the use of statistics in real-world contexts. Over the course of a semester of psychological statistics, two classes completed multiple application exercises designed to mimic real-world contexts; three control classes did not complete the exercises. At the end of the semester, all classes completed questions to assess transfer of statistical knowledge and answered a question that addressed how statistics apply to their everyday lives. Results indicated that students who previously participated in the application exercise activities displayed a greater usage of statistical knowledge when answering far-transfer questions and mentioned real-world applications of statistics more often compared to control students. We discuss the implications of transfer-promoting interventions in equipping students with statistical knowledge that they can flexibly apply in more real-world situations.